Botanical identification of native species most important of dairy basins Molinopampa, Pomacochas and Leymebamba, Amazonas, Peru - Oliva, Manuel (2015)
The objective of this research was conducted botanical identification of native grass species that predominate in the three major livestock department of Amazonas basins (Peru): Molinopampa, Pomacochas and Leymebamba. To select eleven species were surveyed 293 farmers distributed stratified manner in the three basins. The methodology consisted of an examination and recognition of morphological characters of qualitative and quantitative in each of the specimens with the help of laboratory equipment, and then formulates a database order. After identifying each specimen proceeds to develop a database of structural and phenological characteristics. Also, comparisons are made with collections of specimens in herbaria national and foreign herbaria.